On Proximity of Correlation Functions of Homogeneous and Isotropic Random Fields Whose Spectral Functions Coincide on a Certain Set - Pavlov, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We give examples of application of the mean-value theorem to finding various estimates of the proximity of correlation functions in the case where their spectral functions coincide on a certain set.